What does Norway get out of its oil fund, if not more strategic infrastructure investment? - Michael Hudson (Levy Economics Institute of Bard College, 2011)
For the past generation Norway has supplied Europe and other regions with oil, taking payment in euros or dollars. It then sends nearly all this foreign exchange abroad, sequestering its oil-export receipts - which are in foreign currency - in the oil fund to invest mainly in European and US stocks and bonds. The fund now exceeds 500 billion, second in the world to that of Abu Dhabi. It is claimed that treating these savings as a mutual fund invested in a wide array of US, European, and other stocks and bonds (and now real estate) avoids domestic inflation that would result from spending more than 4 percent of the returns to this fund at home. But the experience of sovereign wealth funds in China, Singapore, and other countries has been that investing in domestic infrastructure serves to lower the cost of living and doing business, making the domestic economy more competitive, not less. This paper cites the debate that extends from US 19th-century institutional doctrine to the approach of long-time Russian Chamber of Commerce and Industry President Yevgeny Primakov to illustrate the logic behind spending central bank and other sovereign foreign-exchange returns on modernizing and upgrading the domestic economy rather than simply recycling the earnings to US and European financial markets in what looks like an increasingly risky economic environment, as these economies confront debt deflation and increasing fiscal tightness.
Keywords: H27; H50; H54; H60; 330; sovereign wealth funds; Norway; oil fund